2017
DOI: 10.22158/rem.v2n1p30
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Interest Rates, Income, GDP Growth and House Prices

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 3 publications
2
21
1
Order By: Relevance
“…However, this might change in a few years, depending on global economic development. In contrast, the purchase of land is a very hot topic now (#6) [80,81], with limited availability of unoccupied land meaning that economic risks play an important role when selecting potential sites (#5). In times of accommodative monetary policies and low interest rates, the risk related to inflation is negligible (#6).…”
Section: Discussionmentioning
confidence: 99%
“…However, this might change in a few years, depending on global economic development. In contrast, the purchase of land is a very hot topic now (#6) [80,81], with limited availability of unoccupied land meaning that economic risks play an important role when selecting potential sites (#5). In times of accommodative monetary policies and low interest rates, the risk related to inflation is negligible (#6).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that Gross Domestic Product (GDP), money supply, inflation, lending rates, unemployment rates, and stock price are several variables that focus on explaining residential property prices. Real Gross Domestic Product (GDP) is widely recognized as an important economic factor determinant of residential property price movements (Case & Glaeser, 2000;De Wit & Van Dijk, 2003;Ong, 2013;Xu, 2017). According to Tsatsaronis and Zhu (2014), real GDP growth has information that contains direct measures of household income and housing prices.…”
Section: Macroeconomic Drivers Towards Residential Property Pricesmentioning
confidence: 99%
“…Lending Rate is another important factor determinant of residential property price volatility (Harris, 1989;Qi, 2007;Xu, 2017). Harris (1989) found that housing prices are affected by lending rates.…”
Section: Macroeconomic Drivers Towards Residential Property Pricesmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater number of the studies emphasized the strong relationship between property prices and GDP, as well as demographic factors (Bujang et al , 2010; Gao and He, 2014; Zandi et al , 2015; Aizenman et al , 2016; Reed, 2016; Xu, 2017). However, there is no consensus among various authors and analysts regarding this issue and outcomes are quite complicated.…”
Section: Literature Reviewmentioning
confidence: 99%